Faktor-faktor yang mempengaruhi penggunaan MOOCS dalam kalangan pelajar - Santa, anak Serdin (Universiti Malaysia Sarawak (UNIMAS), 2015)
MOOCs is acknowledged by many as one of the latest trend in e-leaming. This study identified the factors that affect the use of MOOCs among UNIMAS students. UNlMAS has recently established their own MOOCs in the subject of ICT Competency. The Unified Theory of Acceptance Technology (UTAUT) was used to examine the acceptance of students toward this MOOCs. This study used Pearson correlation to determine the relationships between the different aspects ofUTAUT. Regression was used to determine the strength of the relationship of the factor of using the MOOCs. Performance expectancy and social influence are two aspects that are positively related to this acceptance.